2011
DOI: 10.1371/journal.pone.0019352
|View full text |Cite
|
Sign up to set email alerts
|

CD4-Independent Human Immunodeficiency Virus Infection Involves Participation of Endocytosis and Cathepsin B

Abstract: During a comparison of the infectivity of mNDK, a CD4-independent human immunodeficiency virus type 1 (HIV-1) strain, to various cell lines, we found that HeLa cells were much less susceptible than 293T and TE671 cells. Hybridoma cells between HeLa and 293T cells were as susceptible as 293T cells, suggesting that cellular factors enhance the mNDK infection in 293T cells. By screening a cDNA expression library in HeLa cells, cystatin C was isolated as an enhancer of the mNDK infection. Because cathepsin B prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 61 publications
3
25
0
Order By: Relevance
“…These results are consistent with our in-vitro findings that HIV infection upregulates secretion of active cathepsin B by cultured MDM [12]. Two recent studies have suggested roles for cathepsin B in HIV infection [31] and/or release from infected cells [32], but in our study, we found no correlation of cathepsin B levels with plasma HIV-1 RNA copy number or viral load. Previous studies showed that cystatin B expression is induced in cultured MDM after HIV infection [17], and this protein has been associated with HIV replication in MDM [33].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with our in-vitro findings that HIV infection upregulates secretion of active cathepsin B by cultured MDM [12]. Two recent studies have suggested roles for cathepsin B in HIV infection [31] and/or release from infected cells [32], but in our study, we found no correlation of cathepsin B levels with plasma HIV-1 RNA copy number or viral load. Previous studies showed that cystatin B expression is induced in cultured MDM after HIV infection [17], and this protein has been associated with HIV replication in MDM [33].…”
Section: Discussionsupporting
confidence: 93%
“…However, high levels of cystatin C prevented the secretion of cathepsin B but did not diminish its activity. These findings are confirmed by studies that reported the sequestration of cystatin C in the cytoplasm, increased levels of intracellular enzyme, and a concomitant decrease in extracellular levels during late HIV infection (Yoshii et al 2011). This could be a mechanism of cellular protection against increments in cytoplasmic cathepsin B released from lysosomes after infection.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, there is evidence that different Env glycoproteins can direct the virus entry through distinct routes. Entry of some CD4-independent HIV strains appears to require low pH and endocytic machinery [10,54,55]. Also, the block for the HIV-2 MCR infection in non-permissive cells can be rescued by pseudotyping this virus with HIV-1 Env, by inhibiting clathrin-/dynamin-dependent uptake or by disrupting actin filaments [56,57].…”
Section: A Model For Hiv Entry and Fusionmentioning
confidence: 99%